2023
DOI: 10.1093/sleep/zsad167
|View full text |Cite
|
Sign up to set email alerts
|

Does providing feedback and guidance on sleep perceptions using sleep wearables improve insomnia? Findings from “Novel Insomnia Treatment Experiment”: a randomized controlled trial

Abstract: Study Objectives Insomnia is a disorder diagnosed based on self-reported sleep complaints. Differences between self-reported and sensor-based sleep parameters (sleep-wake state discrepancy) are common but not well-understood in individuals with insomnia. This two-arm, parallel-group, single-blind, superiority randomised controlled trial examined whether monitoring sleep using wearable devices and providing support for interpretation of sensor-based sleep data improved insomnia symptoms or imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…As Western health systems increasingly adopt digital health interventions including sleep (see Arroyo and Zawadzki [38] for a systematic review on mHealth interventions in sleep), objective and reliable tracking of the effects of such interventions becomes more and more relevant and allows for ecologically valid and continuous measurements [9] in natural home settings. Recently, for example, Spina et al [11] used sensor-based sleep feedback in a sample of 103 participants suffering from sleep disturbances and found that such sensor-based sleep feedback can already reduce some of the insomnia symptoms. Interestingly, such feedback alone was however not enough to induce changes in the sleepwake misperception, which may need additional interventions (see Hinterberger et al [39]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Western health systems increasingly adopt digital health interventions including sleep (see Arroyo and Zawadzki [38] for a systematic review on mHealth interventions in sleep), objective and reliable tracking of the effects of such interventions becomes more and more relevant and allows for ecologically valid and continuous measurements [9] in natural home settings. Recently, for example, Spina et al [11] used sensor-based sleep feedback in a sample of 103 participants suffering from sleep disturbances and found that such sensor-based sleep feedback can already reduce some of the insomnia symptoms. Interestingly, such feedback alone was however not enough to induce changes in the sleepwake misperception, which may need additional interventions (see Hinterberger et al [39]).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there are undeniably benefits of using accurate wearable devices that affordably capture daily sleep changes in natural environments, outside of the laboratory. Especially in light of recent studies showing that implementing such technologies together with sleep intervention protocols can have positive therapy outcomes [10][11][12][13]. It is our opinion that such technologies, if optimized and carefully validated, will soon play a central role in research and clinical practice as they allow continuous sleep measurements (and feedback) in ecologically valid home environments and at an affordable cost.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, providing feedback on sleep seems to be beneficial regarding insomnia severity and sleep disturbances in individuals with significant insomnia symptoms (Spina et al, 2023). However, it is also important to note, that despite potential improvements in sleep parameters and SOSD, it is not yet fully understood, whether reporting feedback on objective sleep might also possibly result in negative effects, for example, an increase of obsession with sleep due to selected attention, a key pathological feature of insomnia.…”
Section: Discussionmentioning
confidence: 99%
“…Further, recent development of sleep-measuring wearables sees these devices increasingly integrated into sleep interventions (Glazer Baron et al, 2022). For example, one study provided regular feedback on wearable-measured sleep for individuals with insomnia (Spina et al, 2023), and another added wearable-enabled sleep data synchronisation to a digital behavioural therapy to demonstrate greater engagement and improvements in sleep (Aji et al, 2022). Real-world sleep-wake patterns from wearable devices have also been implemented to recommend personalised sleep schedules to maximise alertness (Song et al, 2023).…”
Section: Individual-focused Adaptationmentioning
confidence: 99%